2022
DOI: 10.1126/sciadv.abo2431
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spatial and genomic characterization of coral-associated microbial aggregates in the coral Stylophora pistillata

Abstract: Bacteria commonly form aggregates in a range of coral species [termed coral-associated microbial aggregates (CAMAs)], although these structures remain poorly characterized despite extensive efforts studying the coral microbiome. Here, we comprehensively characterize CAMAs associated with Stylophora pistillata and quantify their cell abundance. Our analysis reveals that multiple Endozoicomonas phylotypes coexist inside a single CAMA. Nanoscale secondary ion mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 101 publications
1
46
0
Order By: Relevance
“…Potential mechanisms of action. The findings of positive correlations between Endozoicomonas, host growth rate, and host disease susceptibility documented in this study complement and contextualize much of the ongoing work on the mechanisms underlying proposed coral-Endozoicomonas metabolic mutualism (39,43) and suggest that the interaction of Endozoicomonas with coral disease susceptibility deserves greater scrutiny. They also echo findings of correlations between life-history strategy and microbiome structure in other important marine invertebrates, such as that between predator defense and microbial abundance in marine sponges (44).…”
Section: Endozoicomonas May Mediate Growth-defense Tradeoffs During C...supporting
confidence: 70%
See 2 more Smart Citations
“…Potential mechanisms of action. The findings of positive correlations between Endozoicomonas, host growth rate, and host disease susceptibility documented in this study complement and contextualize much of the ongoing work on the mechanisms underlying proposed coral-Endozoicomonas metabolic mutualism (39,43) and suggest that the interaction of Endozoicomonas with coral disease susceptibility deserves greater scrutiny. They also echo findings of correlations between life-history strategy and microbiome structure in other important marine invertebrates, such as that between predator defense and microbial abundance in marine sponges (44).…”
Section: Endozoicomonas May Mediate Growth-defense Tradeoffs During C...supporting
confidence: 70%
“…If symbiosis with Endozoicomonas did play a causal role in coral life-history tradeoffs, we hypothesized that we would see a positive correlation between a beneficial coral trait and Endozoicomonas that counterbalances the correlation between Endozoicomonas and disease. Given that Endozoicomonas is thought to be a metabolic mutualist of corals, and it has recently been suggested to facilitate faster coral growth (43), growth rate seemed like a likely candidate for a potential benefit explaining the persistence of coral-Endozoicomonas associations. Depending on the mechanism of action, any such Endozoicomonas -growth correlations might depend merely on the presence of Endozoicomonas, or alternatively on its relative abundance.…”
Section: Coral Opportunist Abundance In Healthy Corals Does Not Predi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wada et al. ( 21 ) also used LCM to sample single CAMAs and confirmed with 16 S rRNA gene metabarcoding the presence of two to three Endozoicomonas strains within individual CAMAs of S. pistillata . Because we pooled many CAMAs in our samples and used a genus-wide Endozoicomonas FISH probe, we cannot assess whether several strains co-occur in a single CAMA in P. acuta .…”
Section: Resultsmentioning
confidence: 91%
“…CAMAs have since been described in numerous cnidarian species, including hard corals, soft corals, and anemones, regardless of disease status, and are particularly common in the genera Acropora , Pocillopora , Porites , Platygyra , and Stylophora ( 14 23 ). Apart from their location and distribution within the coral host, knowledge on CAMAs is scarce, with a handful of studies applying taxon-specific histological techniques to identify bacteria residing in CAMAs ( 16 , 19 , 23 , 24 ), and only one recent study applying culture-independent genomics to assess their functional potential ( 21 ). These studies have shown that bacteria residing in CAMAs often belong to the Endozoicomonas genus, a widespread coral symbiont ( 24 ).…”
Section: Introductionmentioning
confidence: 99%